Age‐dependent variations of scalp thickness in the area designated for a cochlear implant receiver stimulator. Issue 6 (29th October 2018) - Ungar, Omer J.; Amit, Uri; Cavel, Oren; Oron, Yahav; Handzel, Ophir
Abstract : Objective: The integrity of the scalp overlying a cochlear implant receiver stimulator (RS) is critical for the long‐term survival of the implant. Exposure or extrusion of the device will likely result in the need for its removal. There is a global trend of acceleration of population aging, thus raising the prevalence of cochlear implantation (CI) in the elderly. The aim of this study was to define age‐dependent changes in scalp thickness and discuss the implication of that anatomical characteristic for CI in the geriatric population. Methods: Scalp thickness over the location of the RS in the temporo‐parietal area was measured directly with a needle in patients of various ages. Results: Two‐hundred thirty‐six temporo‐parietal scalps were measured in patients aged 18 to 85 years. A strong inverse correlation was found between age and scalp thickness (rs = ‐0.723, P < .001). Scalp thickness decreased with age from a mean of 8 mm in the third decade of life to 5 mm in the ninth decade of life. Conclusion: The human scalp thins with age and most likely undergoes a reduction in its strength. As a consequence, implantable hearing devices that are shielded by the scalp can be at increased risk of exposure and extrusion in the aging recipient. This needs to be taken into account when considering an implantation procedure, the surgical approach and patient instructions on need for and venues for continuing care over time. Level of Evidence: 2B